Calm in the chaos: Targeting mTOR to reduce glioma-driven neuronal hyperexcitability - Karreman, Matthia A.; Venkataramani, Varun (Neuron, 2025)
Primary brain tumors induce neuronal hyperexcitability, leading to epileptic seizures. In this issue of Neuron, Goldberg et al.1 demonstrate genetic, structural, and functional alterations to excitatory tumor-associated neurons and how mTOR inhibition rapidly reverses these changes in a mouse model.